The progressive control of foot-and-mouth disease (FMD) in the Republic of Kazakhstan: Successes and challenges - Sultanov, Akhmetzhan A.; Tyulegenov, Samat; Yessembekova, Gulzhan N.; Berdikulov, Maksat A.; Mukhanbetkaliyev, Yersyn; Akhmetzhanova, Amina; Perez, Andres M.; Abdrakhmanov, Sarsenbay K. (Frontiers in Veterinary Science, 2023)
Foot-and-mouth disease (FMD) has historically caused far-reaching economic losses to many regions worldwide. FMD control has been problematic and the disease is still prevalent in many countries in West and Central Asia. Here, we reviewed the progress made by Kazakhstan in achieving freedom from FMD and discuss some of the challenges associated with maintaining the FMD-free status, as evidenced by the occurrence of an outbreak in 2022. The implementation of a combination of zoning, movement control, vaccination, and surveillance strategies led to the elimination of the disease in the country. However, the circulation of FMD virus in the region still imposes a risk for Kazakhstan and coordinated strategies are ultimately needed to support disease elimination. The results presented here may help the design of effective pathways to progressively eliminate the disease in West and Central Asia, while promoting the design and implementation of regional actions to support FMD control.